Konsep Selibat Pada Masa Intertestamental Dan Tinjauan Teologis Terhadap Selibat Gereja Katolik - Thomas Bedjo Oetomo; Ivan Kurniawan Waruwu (Jurnal Missio Cristo, 2022)
The church is the body of Christ and Christ is the head of the church. This metaphor of the relationship between the church and Christ, intends to illustrate that the dynamics of church life must be centered on Christ. The church must not put church rules beyond the Bible which is the word of Jesus Christ. The establishment of certain spiritual principles must not undermine other spiritual principles. Celibacy is one of the efforts to uphold the principle of chastity and chastity in fulfilling the calling of service. But if celibacy becomes a law for the ordination of a clergyman, then it can undermine the spiritual principle of building a sacred and lasting home. In the Catholic Church, celibacy is following or practicing what is written in the Bible. But to produce proper application, accurate interpretation is needed. Pay attention to the literal, grammatical, historical, and contextual meaning. Thus, the church can find the meaning intended by the author of the book, not an assumption, whose truth is very subjective. Abstrak Bahasa Indonesia Gereja adalah tubuh Kristus dan Kristus adalah kepala gereja. Metafora relasi antara gereja dengan Kristus ini, hendak menggambarkan bahwa dinamika kehidupan gereja harus berpusat pada Kristus. Gereja tidak boleh meletakkan aturan gereja melampaui Alkitab yang adalah firman Yesus Kristus. Penegakkan prinsip rohani tertentu tidak boleh merusak prinsip rohani yang lain. Selibat adalah salah satu usaha untuk menegakkan prinsip kesucian dan kemurnia dalam memenuhi panggilan pelayanan. Namun jika selibat menjadi suatu undang-undang pentahbisan seorang rohaniwan, maka hal tersebut dapat merusak prinsip rohani membangun rumah tangga yang sakral dan langgeng. Dalam kalangan Gereja Katolik, selibat adalah meneledani atau mempraktekkan apa yang tertulis dalam Alkitab. Tetapi untuk menghasilkan penerapan yang tepat, dibutuhkan interpretasi yang akurat. Memperhatikan arti literalnya, gramatikal, historikalnya, dan kontekstualnya. Dengan demikian, gereja dapat menemukan arti yang dimaksud penulis kitab, bukan sebuah dugaan, yang kebenarannya sangat subyektif.